Behavior of functionally graded carbon nanotube reinforced composite sandwich beams with pultruded GFRP core under bending effect - Madenci, Emrah; Özkılıç, Yasin Onuralp; Bahrami, Alireza; Hakeem, Ibrahim Y.; Aksoylu, Ceyhun; Asyraf, Muhammad Rizal Muhammad; Beskopylny, Alexey N.; Stel’makh, Sergey A.; Shcherban’, Evgenii M.; Fayed, Sabry (Frontiers in Materials, 2024)
A novel generation of composite sandwich beams with laminated carbon fiber-reinforced polymer (CFRP) skins and pultruded glass fiber-reinforced polymer (GFRP) core materials are examined for their flexural behavior. The strength and failure mechanisms of the composite sandwich beams in flatwise and edgewise configurations were investigated using three-point static bending tests. These sophisticated compo-site structures must be designed and used in a variety of sectors, and our research provides vital insight into their performance and failure patterns. In comparison to the reference samples (FGM-1), the carbon nanotube-reinforced samples' bending load-carrying capability improved and ranged from -2.5% to 7.75%. The amount of carbon nanotube addition had a substantial impact on the beam's application level and load-carrying capability. Particularly, the application of 0.5 wt% additive in the outermost fiber region of the beam, such as in FGM-4, led to an increase in bending strength. However, the stiffness values at the maximum load were observed to decrease by 0.3% to 18.6% compared to FGM-1, with the minimum level of decrease in FGM-4. The experimental results were compared with theoretical calculations based on the high-order shear deformation theory, which yielded an approximation between 11.99% and 12.98% by applying Navier's solution.